Threats to public health workers - Jennifer A. Horney; Akash Harjivan; Kahler W. Stone; Meredith A. Jagger; Kristina W. Kintziger (Elsevier, 2023)
Media reports and data from public health professional membership organizations have demonstrated high levels of harassment experienced by public health workers throughout the COVID-19 response. We documented personal and political threats to public health workers across the first 12 months of pandemic response through a longitudinal survey completed in Fall 2020 and Summer 2021. The web-based survey was distributed to respondents using the Qualtrics survey platform. Survey items measured domains including demographic information, public health roles and training, mental and physical health, and work-life balance. Respondents were also asked if they had received any personal or political threats, from whom these threats were received, and completed an open-ended question describing the nature of the threats. Among the 85 public health workers completing both surveys, threats from members of the public and from elected and appointed leaders were most prevalent at both timepoints; however, as the pandemic response progressed, the nature of threats to public health workers changed. While those remaining in the public health workforce may be more resilient to these threats, increased prevalence of personal and political threats has the potential to deter new graduates from entering the field, impacting the public health system's future response capacity.